THE ESTABLISHMENT OF ISLAMIC DWELLING PRINCIPLES FOR THE MALAYSIAN COMMUNITIES - Wan Ismail, Wan Norisma; Arabi, Fadli; Mohd Husini, Elina; Zolkifly, Fatin Nur Sakinah; Md. Darus, Zuhairuse; Abd. Jaafar, Nor Haslina; Abd Manaf, Azhani (PLANNING MALAYSIA, 2017)
Strong family ties built on the teachings of the Quran and Sunnah produce excellent foundation in forming a household which are constantly under the protection and blessing of Allah and in turn contribute to the overall health of a community. A dwelling filled with the remembrance of Allah will no doubt find an aura of peace and tranquillity. This is called a home, a place for a family to worship Allah, to relax body and mind, enjoy legitimate worldly delights, teach, learn and propagate the message of Islam. Therefore, provision and design of a dwelling should be considered important to make it a blessed home. This includes the provision of spaces for religious activities, daily basic chores of households, social production, reproduction hygiene needs, privacy and security. Cultural, religious and sustainable aspects of inhabitants should be considered in the planning and design process of a dwelling in the Malaysian context. The Syariah sources have provided basis for its design to conform to Islamic criteria, thereby facilitating various ibadah activities for the inhabitants and users. A review of theory and philosophy of dwelling from Islamic perspective is analysed to justify the comprehensive living approach as promoted by Islam. This paper aims to review literature pertaining to housing principles in Islam and to present basic principles for developing housing criteria based on Islamic teachings.